Adoption of Blockchain-Based Electronic Bills of Lading: Implications for Maritime Business Education and Industry Practice - Nur Achmad Jabrial; Sukardi; Mardiana; Arief Supriatna; Ishak Trianda (Meteor STIP Marunda, 2025)
The digitalization of maritime trade documentation through blockchain-based electronic bills of lading (eBL) represents a transformative innovation with profound implications for shipping operations and maritime business education. This study investigates eBL adoption dynamics from dual industry practice and educational preparation perspectives, examining factors influencing technology acceptance and identifying gaps between industry requirements and academic curriculum coverage. Employing a mixed qualitative methodology, the research analyzes perspectives from logistics professionals (n=45), early adopter organizations (n=12), and maritime business program coordinators (n=15) across Indonesian and regional maritime education contexts. Through thematic analysis integrating Technology Acceptance Model constructs, the study reveals that perceived operational efficiency, trust mechanisms, regulatory recognition, and ecosystem interoperability constitute critical adoption determinants. Findings demonstrate significant disparities between rapid industry transformation toward digital trade documentation and the limited academic coverage of blockchain technologies, eBL platforms, and digital shipping operations within maritime business curricula. The research proposes a comprehensive educational framework integrating blockchain fundamentals, eBL platform functionality, smart contract applications, and hands-on digital documentation simulations. Results provide actionable guidance for curriculum modernization, addressing the urgent need for graduates equipped with digital trade documentation competencies essential for contemporary maritime logistics careers.